Adsorptive removal of phenol using banyan root activated carbon. Issue 6 (3rd May 2021) - Nirmala, Gnanasundaram; Murugesan, Thanapalan; Rambabu, K.; Sathiyanarayanan, K.; Show, Pau Loke
Abstract: Adsorption is an easy and efficient technique for phenolic wastewater treatment. The present study highlights the preparation, characterization and application of activated carbon obtained from the banyan tree's aerial root waste for phenol removal studies. The banyan root activated carbon (BRAC) was chemically modified using potassium hydroxide (KOH) as the activation agent. Various characterization studies revealed the highly porous structure of BRAC with a considerable amount of functional groups present on its surface. Surface area analysis showed a specific surface area of 988 m 2 /g (BET method) and average pore radius of 24 nm (BJH method). Studies on the relationship between adsorption parameters and adsorption performance indicated that the BRAC possessed a maximum phenol removal efficiency of 89.2% for the optimized values of the adsorption parameters. Thermodynamic investigations showed that the adsorption process was spontaneous and exothermic in nature. Further, the phenol adsorption on BRAC conformed to Langmuir model with a theoretical maximum adsorption capacity of 26.95 mg/g. Kinetic analysis revealed that the phenol adsorption on BRAC followed pseudo-second order model. Reusability studies revealed that BRAC can be reused for a maximum of three cycles for continual phenol adsorption from its aqueous streams. Thus, banyan root waste assures to be a potential and economical biomass for production of activated carbon towards the adsorptive treatment of phenol contaminated wastewater streams.